Myocardial revascularization by percutaneous coronary intervention in senile patients with chronic total occlusion: a modern view of the problem - E. R. Atamanyuk; R. S. Tarasov; A. G. Tyryshkin (Российский кардиологический журнал)
In recent decades, the problem of coronary artery disease (CAD) accompanied by chronic total occlusion (CTO) has come to the fore in senile patients. The reason for this is the absence of generally accepted management strategies for these groups of patients. The choice of myocardial revascularization method in elderly patients has a fundamental impact on outcomes, but requires additional research. There is no doubt that in recent years, percutaneous coronary intervention (PCI) in CTO has gained a status as the first-choice method for this pathology. The following main reasons are distinguished: development of intravascular imaging; improvement of surgical instruments; development of new approaches to recanalization; increase in the number of experienced surgeons. The use of PCI for CTO in elderly patients is specified by the upward trend in the proportion of senile population worldwide. This review considers the validity and potential of using PCI for CTO in senile patients, as well as its safety, benefits and prospects. For this review, the following databases were used: Medline (PubMed), RSCI (eLIBRARY), Google Scholar.